A new species in the genus Pseudorhyncomyia Peris, 1952 and the identity of P. deserticola Zumpt and Argo, 1978 (Diptera, Rhiniidae) - Rognes, Knut (Zootaxa, 2013)
The genus Pseudorhyncomyia Peris, 1952 is re-described and shown to have two valid species: P. braunsi (Villeneuve, 1920) and P. aethiopica sp. nov. The latter is described on the basis of a single male specimen captured near Ado, Ethiopia, in 1953. Nominal species P. deserticola Zumpt and Argo, 1978 is transferred to Zumba Peris, 1951, where it is placed as a junior synonym of Z. antennalis (Villeneuve, 1929), syn. nov.